2021
DOI: 10.1021/acsaem.1c00670
|View full text |Cite
|
Sign up to set email alerts
|

Chemical-Pressure-Induced Point Defects Enable Low Thermal Conductivity for Mg2Sn and Mg2Si Single Crystals

Abstract: The development of thermoelectric (TE) materials, which can directly convert waste heat into electricity, is vital to reduce the use of fossil fuels. Mg 2 Sn and Mg 2 Si are promising TE materials because of their superior TE performance. In this study, for future improvement of the TE performance, point defect engineering was applied to the Mg 2 Sn and Mg 2 Si single crystals (SCs) via boron (B) doping. Their crystal structures were analyzed via white neutron holography and SC X-ray diffraction. Moreover, nan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
23
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 61 publications
2
23
0
Order By: Relevance
“…In other words, V Mg and Ga atoms are considered to be point defects. The dislocation core with a density lower than ∼3 × 10 16 cm –2 does not effectively decrease κ lat ; ,, thus, phonon scattering by dislocation cores in the Mg 2 Sn 1– x Ga x SCs is neglected in this study (the calculation details for κ el , κ bip , and κ lat can be found in the Supporting Information and the parameters are presented in Tables S3 and S4). The calculated κ lat curve and the measured κ lat values are plotted against Γ as shown in Figure c.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In other words, V Mg and Ga atoms are considered to be point defects. The dislocation core with a density lower than ∼3 × 10 16 cm –2 does not effectively decrease κ lat ; ,, thus, phonon scattering by dislocation cores in the Mg 2 Sn 1– x Ga x SCs is neglected in this study (the calculation details for κ el , κ bip , and κ lat can be found in the Supporting Information and the parameters are presented in Tables S3 and S4). The calculated κ lat curve and the measured κ lat values are plotted against Γ as shown in Figure c.…”
Section: Resultsmentioning
confidence: 99%
“…Figure 3a shows a high-magnification TEM image of the x = 0.005 ingot, which contains stripe patterns, that is, Moirépatterns, corresponding to the V Mg region, where V Mg aggregated as reported for undoped, Sb-doped, and B-doped Mg 2 Sn SCs. 20,22,24 The other regions have few or no V Mg , resulting in a perfect arrangement of the Ga-doped Mg 2 Sn(111) surface, which is called the single-crystal region. V Mg regions were also found in the high-magnification TEM image of the x = 0.01 ingot (Figure S3).…”
Section: ■ Experiments and Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…9,10 An effective approach to improve the thermoelectric properties of Mg-based II-IV semiconductors is the combination of single crystals and doping. [11][12][13][14][15][16] In polycrystals, there exist many grain boundaries of large crystallographic angle difference, which can act not only as scatterers of carriers but also as trapping sites. Additionally, they can make interface energy levels that can cause band bending through the pinning effect.…”
mentioning
confidence: 99%